"Kann jemand, der diese Musik gehört hat, […] noch ein schlechter Mensch sein?" – om Wieslers forandring og kunstens påståtte rolle i denne prosessen - Skare, Roswitha (Nordlit, 2012)
The Life of Others (2006) has been a successful film, winning the Oscar for Best Foreign Feature in 2007. It is a film about surveillance, but also about the lives of artists and writers in East Berlin in the middle of the 1980s, and about what role literature and art played in the GDR and in the events of autumn 1989. The article focuses on the way the film portrays Wiesler’s transformation from hard-boiled Stasi officer into the guardian angel of his target, and shows how art – both literature and music – plays an important role in this process.